Pola asuh demokratis orangtua pada saat pandemi covid-19 - Baharuddin Baharuddin (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2020)
The coronavirus pandemic (COVID-19) gives an impactonthe lives of all families throughout the world. There are so many activities such as learning, working and event religious activities being asked to take place from home, while appeals to keep a safe physical distance from others continue to be called out so that all children's activities are carried out at home. In the current condition, the child may experience a condition that is less stable and even impaired his physical and mental health. The current condition of the Covid-19 pandemic needs to pay attention to family members, especially children, every parent should alwaysbe there when the child needs and wants to communicate well with parents. Therefore, it is a must for the parents to provide comfort to children from various productive activities or activities. The importance of applying democratic parenting,showing and paying respect tonon- absolutefreedom, with affectionate guidance between children and parents, providing a rationale and objective explanation of thechildrenâ€™srequests and opinions are not appropriate. In this parenting,Â children will learn a sense of responsibility and the ability to act following existing norms and doing activities at home properly including the learning process. This research is a qualitative study that focuses on the phenomenology in the events that occurred during the Covid-19 pandemic regarding democratic parenting towards children while staying at home. Democratic parenting mentioned in this research is by educating children, establishing good communication in which parents still determine the rules but considering the situation and always provide support and needs of children.Pandemi virus corona (COVID-19) memberikan dampak kehidupan semua keluarga di seluruh dunia. Ada begitu banyak kegiatan seperti belajar, bekerja dan acara kegiatan keagamaan yang diminta berlangsung dari rumah, sementara imbauan untuk menjaga jarak fisik yang aman dari orang lain terus dipanggil agar semua kegiatan anak dilakukan di rumah. Dalam kondisi saat ini, anak mungkin mengalami kondisi yang kurang stabil dan bahkan terganggu kesehatan fisik dan mentalnya. Kondisi pandemi Covid-19 saat ini perlu memperhatikan anggota keluarga, terutama anak-anak, setiap orang tua harus selaluber di sana ketika anak membutuhkan dan ingin berkomunikasi dengan baik dengan orang tua. Oleh karena itu, merupakan suatu keharusan bagi orang tua untuk memberikan kenyamanan kepada anak-anak dari berbagai kegiatan atau kegiatan yang produktif. Pentingnya menerapkan pengasuhan demokrasi, menunjukkan dan memberikan penghormatan kepada tonon- absolutefreedom, dengan bimbingan penuh kasih sayang antara anak- anak dan orang tua, memberikan alasan dan penjelasan objektif tentang kekelurakatan dan pendapat anak-anak tidak tepat. Dalam pengasuhan ini, anak-anak akan belajar rasa tanggung jawab dan kemampuan bertindak mengikuti norma-norma yang ada dan melakukan aktivitas di rumah dengan baik termasuk proses pembelajaran. Penelitian ini merupakan studi kualitatif yang berfokus pada fenomena dalam peristiwa yang terjadi selama pandemi Covid-19 mengenai pengasuhan demokrasi terhadap anak selama berdiam diri di rumah. Pengasuhan demokrasi yang disebutkan dalam penelitian ini adalah dengan mendidik anak, menjalin komunikasi yang baik di mana orang tua tetap menentukan aturan namun mempertimbangkan situasi dan selalu memberikan dukungan dan kebutuhan anak.